Smart Electronic Systems on Human Assistance – A Review - Meena, S. P. (Journal of Electronics and Informatics, 2023)
Electronic devices are micro programmed unit that are primarily designed for operate like a control unit on several applications. It is also implemented for doing several data and information processing purposes. The smart electronic devices are structured with a goal to make a connection between one or more devices. In recent years the smart electronic devices are designed to operate based on the command given by a human through voice or signals. In very rare applications the smart electronic devices are programmed to take decision on its own. The purpose of this article is to project the recent advancements in the smart electronic devices on healthcare, communication, automation, robotics and security applications. The article is also further extended to present the recent research growth in the field of smart electronics with its future directions.
Keywords: Smart sensor; wireless communication; intelligent systems; control devices; data transmission; device to device communication